2008
DOI: 10.1371/journal.pgen.0040014
|View full text |Cite
|
Sign up to set email alerts
|

Network Discovery Pipeline Elucidates Conserved Time-of-Day–Specific cis-Regulatory Modules

Abstract: Correct daily phasing of transcription confers an adaptive advantage to almost all organisms, including higher plants. In this study, we describe a hypothesis-driven network discovery pipeline that identifies biologically relevant patterns in genome-scale data. To demonstrate its utility, we analyzed a comprehensive matrix of time courses interrogating the nuclear transcriptome of Arabidopsis thaliana plants grown under different thermocycles, photocycles, and circadian conditions. We show that 89% of Arabidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
730
4
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 500 publications
(802 citation statements)
references
References 65 publications
62
730
4
6
Order By: Relevance
“…qPCR reactions were performed with Brilliant III SYBR Green QPCR Master Mix (Agilent) on a Mx3000P (Agilent Technologies Ltd, Stockport, UK) or a StepOnePlus (Fisher Scientific‐UK Ltd, Loughborough, UK) real‐time PCR system. IRON SULFUR CLUSTER ASSEMBLY PROTEIN 1 ( ISU1 , At4G22220) was used as the reference gene as its expression has been shown not to cycle over a range of conditions (Michael et al ., 2008). All primer sequences are given in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…qPCR reactions were performed with Brilliant III SYBR Green QPCR Master Mix (Agilent) on a Mx3000P (Agilent Technologies Ltd, Stockport, UK) or a StepOnePlus (Fisher Scientific‐UK Ltd, Loughborough, UK) real‐time PCR system. IRON SULFUR CLUSTER ASSEMBLY PROTEIN 1 ( ISU1 , At4G22220) was used as the reference gene as its expression has been shown not to cycle over a range of conditions (Michael et al ., 2008). All primer sequences are given in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…The expression pattern of NFL was monitored during diurnal growth conditions using publicly available data (http://diurnal. mocklerlab.org/) (Michael et al, 2008). NFL expression is regulated under diurnal conditions with a peak at 12-16 h after dawn under SD conditions (Fig.…”
Section: Day-length Is Crucial For Nfl Functionmentioning
confidence: 99%
“…56,57 This analysis suggested that such an extensive control was achieved by dispersed promoter sequences throughout the plant genome that provide a particular time frame of expression. 56,57 These authors also found that at least in one of the conditions tested, more than 10,000 genes were under circadian control, while more than 16,000 were…”
Section: Genome Transcriptional Control By the Circadian Clockmentioning
confidence: 99%